ANALISIS BEBAN KERJA UNTUK MENGOPTIMALKAN TENAGA KERJA PABRIK TAHU X DENGAN METODE WORKLOAD ANALYSIS DAN WORKFORCE ANALYSIS - Cindy Meisya Putri Hidayat, (2021)
Tofu factory X is one of the industries engaged in the food sector, namely by making processed soybeans into tofu. Tofu factory X is one of the tofu factories located in Depok, West Java. Problems that occur in factories are working hours that exceed and do not achieve optimal productivity levels due to the factory's inability to meet all requests, for this reason this study aims to calculate the workload of each worker to know the optimal number of workers according to the workload. with the method of Workload analysis and Workforce analysis, after that, a cost analysis is carried out to assist decision making. Based on the results of the analysis, it was found that 4 workers have a workload that exceeds the normal limit, namely operator 1 of 124%, operator 4 of 116%, operator 5 of 112%, and operator 7 of 111%. Calculation of the optimal workforce using the Workforce analysis method shows that the workers of the tofu factory X are advised to add 4 workers to each workstation with excessive workloads. Based on the cost analysis, the alternative with the lowest cost is chosen by adding overtime hours with details of the costs that come out per two months amounting to RP.5.271.676.30.